A second course in statistics regression analyisis - Mendenhall, William; Sincich, Terry (Pearson Education, Inc., 2020)
"This book is designed for two types of statistics courses. The early chapters, combined with a selection of the case studies, are designed for use in the second half of a two-semester (two-quarter) introductory statistics sequence for undergraduates with statistics or non-statistics majors"-- c Provided by publisher